1995
DOI: 10.1093/clinids/21.6.1402
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Vaginosis in Lesbians: A Sexually Transmitted Disease

Abstract: Sexual transmission of bacterial vaginosis (BV), a common syndrome in sexually active women, has not been previously established. Because no male counterpart for BV has been found, a population of lesbians is an ideal one in which to test the hypothesis that BV is sexually transmitted. We studied 103 homosexual women (lesbians) who sought gynecologic care at a community clinic and in a private gynecology practice in New York City. Participants were asked to refer their sexual partners for evaluation. In this c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
60
0
2

Year Published

1996
1996
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(67 citation statements)
references
References 31 publications
5
60
0
2
Order By: Relevance
“…The relationship with having had sex with a female is consistent with some evidence that female-tofemale transmission of bacterial vaginosis occurs. In a small study of 21 lesbian couples, 72% of partners of women with bacterial vaginosis also had bacterial vaginosis, compared with only 10% of partners of those without bacterial vaginosis 38 .…”
Section: Discussionmentioning
confidence: 97%
“…The relationship with having had sex with a female is consistent with some evidence that female-tofemale transmission of bacterial vaginosis occurs. In a small study of 21 lesbian couples, 72% of partners of women with bacterial vaginosis also had bacterial vaginosis, compared with only 10% of partners of those without bacterial vaginosis 38 .…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, Marrazzo and colleagues, utilizing rep-PCR to characterize vaginal isolates among 30 monogamous (defined within the timeframe of the prior 3 months) female sex partners, revealed that 23 of these couples shared identical strains of Lactobacillus. Finally, other studies have demonstrated that BV is frequently found in both members of monogamous lesbian couples and BV concordance within couples has been associated with specific sexual behaviors, including shared use of vaginally penetrative sex toys [57,58].…”
Section: Bacterial Vaginosismentioning
confidence: 96%
“…The concordance of BV status in monogamous lesbian couples ranges up to 95% (53,54), strongly suggesting that BV is sexually associated, although an infectious correlate has not been identified (55). Menses, a new sexual partner, vaginal douching, receptive oral sex, and lack of condom use are among the strongest risk factors for BV (54,(56)(57)(58)(59)(60)(61)(62)(63).…”
Section: Epidemiology Of Bvmentioning
confidence: 99%